PERAN GANDA PEREMPUAN DALAM BUDAYA PATRIARKI DI INDONESIA MENGGUNAKAN ANALISIS SAID RAMADHAN AL-BUTHI - Fajar Nur Kholifah; Rara Siti Masruroh (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
This paper aims to strengthen the opinion or concept of the dual role of a woman in the public and domestic spheres. This research uses normative descriptive research with juridical-empirical analysis. Based on the results of the study, the author will discuss the patriarchal culture in Indonesia and then examine it using the perspective of Said Ramadhan Al-Buthi. Regarding the dual role of women in the public and domestic spheres, it is a woman's choice. The existing regulations in fiqh, the Compilation of Islamic Law, and the Civil Code in general indicate that one of the obligations of a wife is to obey her husband. Therefore, it is important to have a husband's permission when his wife wants to increase her role in the public sphere. While the obligation to take care of the household is a shared responsibility. Al-Buthi explained that the division of roles in taking care of housework is a contract that must be discussed before marriage. If there is no contract, then customary law applies in that country.